การพัฒนาแบบวัดการคิดอย่างมีวิจารณญาณของนักเรียนมัธยมศึกษาตอนปลายในรายวิชาสังคมศึกษา ศาสนา และวัฒนธรรม โดยประยุกต์ใช้การประเมินแบบพลวัตด้วยคอมพิวเตอร์ - ณณณ์ วรธนพิมกร (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The purposes of this study were (1) to develop and validate the critical thinking scale of upper secondary school students in social studies by applying computerized dynamic assessment, and (2) to compare the critical thinking of upper secondary school students with different learning achievement levels and gender from those measured by the critical thinking scale of upper secondary school students by applying computerized dynamic assessment. Sample consisted of 257 upper secondary school students. The research instrument was the critical thinking scale of upper secondary school students by applying computerized dynamic assessment. Quantitative data were analyzed by using descriptive statistic, item validation, scale validation, independent-sample t-test, one-way ANOVA, and two-way ANOVA. Results revealed that1. The critical thinking scale by applying computerized dynamic assessment was two-tier multiple-choice tests (20 items) measuring four components; i.e., (1) problem formulation, (2) hypothesis identification and application, (3) data classification and judgment, and (4) conclusion. All items and mixed prompting had content validity (IOC index= .8 to 1.0 and .6 to 1.0), the difficulty and discrimination indexes ranged from .45 to .82 and .41 to .82, respectively. Cronbach’s alpha coefficient was .88.2. There was an interaction between learning achievement levels and gender on actual scores, mediation scores, and learning potential scores statistically significant at the level of .05. Means of actual scores, mediation scores, and learning potential scores between high and middle groups, high and low groups, as well as middle and low groups were statistically significant different at the level of .05. In addition, means of actual scores and mediation scores between male and female were not statistically significant different at the level of .05 while learning potential scores between male and female were statistically significant different at the level of .05.